2019
DOI: 10.4236/jcc.2019.711003
|View full text |Cite
|
Sign up to set email alerts
|

Churn Prediction Using Machine Learning and Recommendations Plans for Telecoms

Abstract: Keeping customers satisfied is truly essential for saying that business is successful especially in the telecom. Many companies experience different techniques that can predict churn rates and help in designing effective plans for customer retention since the cost of acquiring a new customer is much higher than the cost of retaining the existing one. In this paper, three machine learning algorithms have been used to predict churn namely, Naïve Bayes, SVM and decision trees using two benchmark datasets IBM Wats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…e sample distribution is modified in the AdaBoost algorithm, which eliminates some of the mistakes from previous iterations [24].…”
Section: Ensemble Learning Techniques Ensemble Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…e sample distribution is modified in the AdaBoost algorithm, which eliminates some of the mistakes from previous iterations [24].…”
Section: Ensemble Learning Techniques Ensemble Learningmentioning
confidence: 99%
“…According to the current studies, these techniques improve the prediction performance according to current studies. For example, Ebrah and Elnasir [24] applied the algorithms (Naive Bayes, support vector machine, and decision tree) to train the dataset to predict customer churn for a telecommunication operator and found that the support vector machine algorithm had better performance. e work of Brandusoiu and Toderean [13] also confirmed the effectiveness of these techniques using logistic regression and SVM.…”
Section: Techniques For Churn Predictionmentioning
confidence: 99%
“…Jain et al [ 15 ] proposed two approaches including Logistic Regression and Logit Boost but the accuracy generated from these methods were lowers than models using kernel tricks introduced in preceding studies which used the same dataset. Furthermore, in [ 3 , 5 , 7 , 10 ], authors showed that kernel Support Vectors Machines gave the best results compared to other techniques. Each real-world dataset has its own properties and kernel tricks are very functional in constructing the type of space and hyperplanes of Support Vector Machine that are suitable with the studied dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Many previous works [ 1 10 ] have confirmed that customer churn prediction depended on complex human behaviors, such as customer data, usage, consumption behavior, and so on.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation